2013
DOI: 10.1210/en.2012-1829
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Controls Adrenomedullary Catecholamine Secretion and Expression of Catecholamine Biosynthetic Enzymes at High Splanchnic Nerve Firing Rates Characteristic of Stress Transduction in Male Mice

Abstract: The neuropeptide PACAP (pituitary adenylate cyclase-activating polypeptide) is a cotransmitter of acetylcholine at the adrenomedullary synapse, where autonomic regulation of hormone secretion occurs. We have previously reported that survival of prolonged metabolic stress in mice requires PACAP-dependent biosynthesis and secretion of adrenomedullary catecholamines (CAs). In the present experiments, we show that CA secretion evoked by direct high-frequency stimulation of the splanchnic nerve is abolished in nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
80
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 24 publications
0
80
0
1
Order By: Relevance
“…Congruently, PACAP is colocalized with acetylcholine in abdominal preganglionic splanchnic nerve terminal terminals innervating the adrenal medulla for epinephrine release. PACAP application increases the excitability of adrenal chromaffin cells (36), and enhances the synthesis and release of adrenal catacholamines (9, 37, 38). Conversely, PACAP knockout mice exhibit disrupted catecholamine release patterns from splanchnic nerve activation and during chronic stress exposure (31, 37), which in aggregate suggest that PACAP is widely distributed throughout the HPA and sympathetic nervous system and is one of the principal facilitators of the endocrine and neuronal responses to stressful challenges.…”
Section: Pacap and The Stress Responsementioning
confidence: 99%
“…Congruently, PACAP is colocalized with acetylcholine in abdominal preganglionic splanchnic nerve terminal terminals innervating the adrenal medulla for epinephrine release. PACAP application increases the excitability of adrenal chromaffin cells (36), and enhances the synthesis and release of adrenal catacholamines (9, 37, 38). Conversely, PACAP knockout mice exhibit disrupted catecholamine release patterns from splanchnic nerve activation and during chronic stress exposure (31, 37), which in aggregate suggest that PACAP is widely distributed throughout the HPA and sympathetic nervous system and is one of the principal facilitators of the endocrine and neuronal responses to stressful challenges.…”
Section: Pacap and The Stress Responsementioning
confidence: 99%
“…This activation is mediated by indirect reflex excitation of the splanchnic nerve, which evokes large increases in catecholamine secretion (resulting in up to 70% of epinephrine content depletion) (47) accompanied by activation of TH enzyme and compensatory catecholamine biosynthesis in the adrenal medulla to maintain cellular catecholamine levels constant (41). As an index of catecholamine biosynthesis, we quantified changes in adrenal TH mRNA (25).…”
Section: Transsynaptic Modulationmentioning
confidence: 99%
“…The PACAP peptide amino acid sequence is highly conserved, and the action of PACAP is tissue specific dependent on the activation of the different isoforms of the seven transmembrane G proteincoupled PACAP-selective PAC 1 receptor (Adcyap1r1) and/or the vasoactive intestinal peptide (VPAC) receptors (2,4,20,45,54). PACAP/PAC 1 receptor signaling modulates synaptic transmission and plasticity via pre-and postsynaptic mechanisms, and these effects have been shown to be critically important in central stress responses, peripheral sensory and autonomic function, and maintenance of physiological homeostasis (9,18,19,21,25,31,32,40,41,47,49,54).We previously identified colocalization of PACAP with acetylcholine in cholinergic parasympathetic preganglionic terminals innervating guinea pig cardiac neurons (5, 6) and demonstrated that both endogenously released and exogenously applied PACAP significantly increases cardiac neuron excitability through PAC 1 receptor activation (5,22,35,49). Cardiac neurons are more readily accessible than CNS neurons for experimental manipulations and accordingly, we have used these cells to further our understanding of cellular PAC 1 receptor signaling mechanisms.…”
mentioning
confidence: 99%
“…The PACAP peptide amino acid sequence is highly conserved, and the action of PACAP is tissue specific dependent on the activation of the different isoforms of the seven transmembrane G proteincoupled PACAP-selective PAC 1 receptor (Adcyap1r1) and/or the vasoactive intestinal peptide (VPAC) receptors (2,4,20,45,54). PACAP/PAC 1 receptor signaling modulates synaptic transmission and plasticity via pre-and postsynaptic mechanisms, and these effects have been shown to be critically important in central stress responses, peripheral sensory and autonomic function, and maintenance of physiological homeostasis (9,18,19,21,25,31,32,40,41,47,49,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation